Simulasi Numerik Persamaan Gelombang Air Dangkal untuk Kasus Bendungan Bobol - Raditya Panji Umbara (Jurnal ALAMI : Jurnal Teknologi Reduksi Risiko Bencana, 2021)
Technological failure and natural disasters that caused the dam-break resulted in huge losses, both material loss and loss of life. The mathematical model for the dam-break can use the shallow water equation. In this paper, modeling the dam-break in two dimensions is solved by using the finite volume method with a stagerred-grid scheme. The staggered-grid scheme produces more accurate and robust when compared to the Lax-Friedrics scheme. The stability of the water waves on the part of the damaged dam wall is also well preserved using a staggered-grid scheme. Modeling a dam-break with real bathymetric data will be a challenge for further research, because it involves a more complex geometry.